A complete folk theorem for finitely repeated games - Ghislain-Herman Demeze-Jouatsa (International Journal of Game Theory, 2020)
This paper analyzes the set of pure strategy subgame perfect Nash equilibria of any finitely repeated game with complete information and perfect monitoring. The main result is a complete characterization of the limit set, as the time horizon increases, of the set of pure strategy subgame perfect Nash equilibrium payoff vectors of the finitely repeated game. This model includes the special case of observable mixed strategies.
Keywords: C72 and C73; 330; Finitely repeated games; Pure strategy; Observable mixed strategies; Subgame perfect Nash equilibrium; Limit perfect folk theorem